Prophetic Instructional Strategies: A Pedagogical Framework for the Contemporary Academics - Fatima, Tehreem; Tasgheer, Aqsa (Journal of Islamic and Religious Studies, 2022)
Prophet Muhammad (PBUH) was not only the preacher of a new religion and the leader of a new community but also an effective teacher, a passionate supporter of learning, and a pioneer of modern education. Islam is a revealed and knowledge-based religion that promotes learning and in which every person regardless of caste, class, color, and gender is obliged to get an education. The early Muslims were passionate about education as they were influenced by Prophet Muhammad's outstanding teaching methods and tactics. The Holy Prophet (PBUH) used every tool and approach available to transmit knowledge to people. The methods and strategies used by the Holy Prophet and the early Muslims in their academic endeavors are examined in this study. This paper explores Hadith literature on instructional methods and proposes a dynamic synthesis of Islamic pedagogical principles, particularly prophetic precepts, with academic ideas of modern education. Such synthesis is compatible with the manifestations of Prophetic precepts spanning Muslim history, and it would provide an explicit Islamic pedagogical framework for teachers, many of whom are from quite diverse educational systems. The research aims to study instructional techniques employed by Holy Prophet (PBUH) in order to promote a modern education system.